Private Participation in the Road Sector in Brazil : Recent Evolution and Next Steps - Véron, Adrien; Cellier, Jacques (World Bank, Washington, DC, 2014)
Today, Brazil has the second longest highway network under private concessions in the world. This paper analyzes Brazil's experience under the two first phases of the federal road concession program, and highlights some of the program's strengths and areas for further development. Despite the unfolding world financial and economic crisis, the potential for further private participation in the sector appears very good. This paper essentially argues that it may be time for Brazil to revamp its current models for private participation in the sector, which may soon reach their limit in terms of being able to meet efficiently the needs of a growing economy. In summary, Brazil could: 1) diversify its toll road model to allow for more innovative public-private partnership structures; 2) update its toll regulatory and contractual framework to overcome some of the design problems that have led to relatively inefficient tolling; 3) consolidate the institutional framework for road concessions to give a stabilized basis for further developments; 4) develop a policy framework adapted to the current Brazilian environment, taking into account the need to ensure harmonized levels of service and tolls across the country; and 5) adapt the sector financing framework to the rising capacity of private markets.